Identifying the Students’ Difficulties in Comprehending TOEFL Reading Test - Dahlan, Dahlan (FOSTER: Journal of English Language Teaching, 2021)
The study aimed to find out the Students’ difficulties in comprehending TOEFL reading Test. The description of the data through the question as explained in the previous section showed that the students have some problems or difficulties in TOEFL. There are five items of the difficulties faced by students of fourth-semester students of IAIN Palopo in the Academic year 2019/2020 about determining the main idea, supporting detail, vocabulary, reference, and inference. Those facts are also backed up by the result of a questionnaire which shows that those items must be considered to be resolved.